2022
DOI: 10.3390/cimb44060168
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Zeaxanthin Alleviates Low Temperature Combined with Low Light Induced Photosynthesis Inhibition and Oxidative Stress in Pepper (Capsicum annuum L.) Plants

Abstract: Low temperature combined with low light (LL) affects crop production, especially the yield and quality of peppers, in northwest China during the winter and spring seasons. Zeaxanthin (Z) is a known lipid protectant and active oxygen scavenger. However, whether exogenous Z can mitigate LL-induced inhibition of photosynthesis and oxidative stress in peppers remains unclear. In this study, we investigated the effects of exogenous Z on photosynthesis and the antioxidant machinery of pepper seedlings subject to LL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…et al, 2020). As reported previous, LL has adverse effects on plant seedlings and results in significant reduction in growth (Li et al, 2021;Ding et al, 2022;Li et al, 2022). Our results demonstrated that the LL-induced inhibition was associated with significant increases in ROS and changes in antioxidant enzymes in pepper seedlings.…”
Section: Discussionsupporting
confidence: 83%
“…et al, 2020). As reported previous, LL has adverse effects on plant seedlings and results in significant reduction in growth (Li et al, 2021;Ding et al, 2022;Li et al, 2022). Our results demonstrated that the LL-induced inhibition was associated with significant increases in ROS and changes in antioxidant enzymes in pepper seedlings.…”
Section: Discussionsupporting
confidence: 83%
“…The APX reduces H 2 O 2 to H 2 O and mono-dehydroascorbic acid (MDHA), using ascorbic acid as a reducing agent, particularly in the cytosol and chloroplast (Ding et al 2022 ). One unit of APX is defined as 1 mM of ascorbate oxidized per min per mg of protein, and the method followed Narwal et al ( 2009 ).…”
Section: Methodsmentioning
confidence: 99%
“…Wu et al [44] found that exogenous NO improved the low-temperature tolerance of plants by improving the ascorbate-glutathione cycle. Exogenous zeaxanthin improved the survival ability of pepper at low temperatures by increasing antioxidant enzymes such as POD and CAT [45].…”
Section: Changes In Mda and Antioxidant Enzymesmentioning
confidence: 99%